¡The archaeological object in the cultural and intellectual tradition of premodern Japan - Abad de los Santos, Rafael (Estudios Complutenses de Asia Oriental, 2025)
This article aims to analyze the interpretations raised by the inhabitants of Japan regarding artifacts and prehistoric sites discovered in the archipelago between Antiquity and the Edo period. Specifically, the responses to the dōtaku (bell-shaped objects) of the Yayoi culture, as well as the shell middens and stone tools of the Jōmon culture, are analyzed. The direct analysis of the primary sources allows observing how the chronological and technological distance between the prehistoric world and premodern Japan, in its different stages, decisively conditioned the answers given before these findings, giving rise to a heterogeneous and disparate reaction. This also reflects the different intellectual and religious currents prior to the country embracing western knowledge, beginning with the Meiji Restoration in 1868.
Keywords: history of archaeology; premodern Japanese thought; Yayoi culture; Jōmon culture; myth of the giant; antiquarianism